2021
DOI: 10.14499/indonesianjcanchemoprev12iss2pp106-113
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangosteen as An Oxidative Inhibitor in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common primary malignancy of the liver and the second leading cause of cancer mortality worldwide. Many strategies to discover molecular-based therapy are currently being implemented to overcome the resistance in HCC treatment. Cancer research is more targeted at molecular level of natural ingredients treatment as chemoprevention to reduce carcinogenesis risk. One of the natural compounds that serve as chemopreventive agent is mangosteen. α-Mangosteen, a xanthone comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Moreover, α-mangostin-induced ROS overproduction might activate the PI3K/AKT signaling pathway, inhibiting cancer cell proliferation, migration, and induction of mitochondrial dysfunction that mediates apoptosis in MDA-MB-231 cells ( 23 ). Another finding also revealed that α-mangostin enhanced higher ROS accumulation in hepatoblastoma HepG2 cells than in hepatocyte WRL-68 cells, which could imply the selectivity of α-mangostin in cells ( 43 ).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, α-mangostin-induced ROS overproduction might activate the PI3K/AKT signaling pathway, inhibiting cancer cell proliferation, migration, and induction of mitochondrial dysfunction that mediates apoptosis in MDA-MB-231 cells ( 23 ). Another finding also revealed that α-mangostin enhanced higher ROS accumulation in hepatoblastoma HepG2 cells than in hepatocyte WRL-68 cells, which could imply the selectivity of α-mangostin in cells ( 43 ).…”
Section: Discussionmentioning
confidence: 92%
“…However, when assessing MdA levels, α-mangostin led to a more significant MDA reduction in the HepG2 cancer line, possibly due to the increased oxidative stress in comparison with the WRL-68 cell line. Notably, when compared to WRL-68, a normal human hepatic cell line, HepG2 cell line presented with a more notable reduction of MdA (109). It is possible that HepG2 presented with more reduced MdA because of the effects of both ROS that stabilizes Nrf2, and oncogenic signaling via KRAS and BRAF that has been revealed to induce Nrf2 stabilization (110), leading to enhanced production of antioxidant proteins.…”
Section: Antioxidant Effects Of α-Mangostinmentioning
confidence: 97%
“…It was reported that the interactions with key amino acid residues of EGFR, i.e., Glycine695, Glycine700, Glutamine767, Methionine769, Aspartic acid831, Glycine833, Arginine812, Asparagine818, and Tyrosine845 were pivotal to the suppression of cancer cell division [7] 2). It was reported that the interactions with Glutamic acid640, Cysteine673, and Aspartic acid810 residues were critical to deactivating the PDGFR function leading to the suppression of cancer cell proliferation [12]. From the molecular docking data, the 1,3,6,8tetrahydroxyxanthone interacted with all these key amino acid residues at the hinge region αC-helix DFG motif of the activation loop of PDGFR.…”
Section: Molecular Docking Of Hydroxyxanthonementioning
confidence: 99%
“…Meanwhile, the interactions of 1,3,6,8tetrahydroxyxanthone with Glutamine767 and Methionine769 through hydrogen bonds, as well as Aspartic acid831 through van der Waals interaction, on the active site of EGFR caused the less signal for the cancer cells to proliferate, differentiate and survive [7] [8]. On the other hand, the ability of 1,3,6,8-tetrahydroxyxanthone to interact with Cysteine673 and Aspartic acid810 through hydrogen bonds on the active site of PDGFR protein receptor, as well as with Glutamine640 through van der Waals, suppress the regulation of cancer cell to migrate, survive and proliferate [12].…”
Section: Molecular Docking Of Hydroxyxanthonementioning
confidence: 99%
See 1 more Smart Citation